1999
DOI: 10.1111/j.1469-7793.1999.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Common modulation of motor unit pairs during slow wrist movement in man

Abstract: The activity of 36 pairs of single motor units were recorded with intramuscular wire electrodes from m. extensor carpi radialis while subjects performed slow wrist extension and flexion movements. Periods of steady position holding were interposed between movements. The discharge trains from pairs of motor units were analysed statistically in the time and frequency domains. During extension movements, when the muscle recorded from was the agonist, coherence between motor units was significant below 12 Hz, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 46 publications
4
69
0
Order By: Relevance
“…Furthermore, there is evidence that synchronization of motor units in the first dorsal interosseus is greater during eccentric compared with concentric contractions (32), which can potentially increase the fluctuations in acceleration (37,47). Alternatively, the fluctuations in acceleration might be a consequence of the common modulation of motor unit discharge (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence that synchronization of motor units in the first dorsal interosseus is greater during eccentric compared with concentric contractions (32), which can potentially increase the fluctuations in acceleration (37,47). Alternatively, the fluctuations in acceleration might be a consequence of the common modulation of motor unit discharge (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…The power spectrum for acceleration has been associated with the discharge pattern of the motor units (16,20), whereas the EMG spectrum has been used to characterize changes in the activation signal sent by the nervous system to the muscle. Preliminary analyses indicated no significant differences (P Ͼ 0.05) in the frequency content of the acceleration and interference EMG (absolute power, median frequency, and the frequency where peak power occurred) for the three trials at a given velocity performed by each subject.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to several previous studies on finger and hand muscles. [20][21][22][23][24][25] Vallbo et al 2 0 observed 10Hz oscillation during slow ramp finger movements and Kakuda et al 2 1 reported 6-12 Hz coherence between motor units during the movement phase of slow finger movements, which decreased during position holding. Thus they suggested that the 6-12 Hz input is specific for movements and is normally absent or much weaker during steady maintenance of position or force.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical activity in the [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz range has been shown to be coherent with oscillatory EMG activity in contralateral hand and forearm muscles in monkeys and humans. 1,[4][5][6][7][8][9] However, the functional significance of this corticomuscular coherence is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Also, several studies used trial durations far shorter than the shortest duration studied here, which would preclude detection of significant coherence except for very high levels. For example, coherence measurements have been applied to trials that were only 5 seconds (Kakuda et al, 1999) and 8 seconds (Kilner et al, 2002) long. The broad range of study parameters demonstrates the need to assess how these choices affect coherence incidence.…”
Section: Discussionmentioning
confidence: 99%